Circadian Clock Proteins and Immunity - O'NEILL, LUKE; CURTIS, ANNIE (My University, 2014)
Immune parameters change with time of day and disruption of circadian rhythms has been linked to inflammatory pathologies. A circadian-clock-controlled immune system might allow an organism to anticipate daily changes in activity and feeding and the associated risk of infection or tissue damage to the host. Responses to bacteria have been shown to vary depending on time of infection, with mice being more at risk of sepsis when challenged ahead of their activity phase. Studies highlight the extent to which the molecular clock, most notably the core clock proteins BMAL1, CLOCK, and REV-ERB?, control fundamental aspects of the immune response. Examples include the BMAL1:CLOCK heterodimer regulating toll-like receptor 9 (TLR9) expression and repressing expression of the inflammatory monocyte chemokine ligand (CCL2) as well as REV-ERB? suppressing the induction of interleukin-6. Understanding the daily rhythm of the immune system could have implications for vaccinations and how we manage infectious and inflammatory diseases
PUBLISHED
Keywords: immune system; Immunology, Inflammation & Infection; CIRCADIAN CLOCK PROTEINS; Immune System; Inflammation